Development of Student Worksheets Based on Discovery Learning for the Plant World Material During the New Normal Learning Period - Ritonga, Indah Lestari; Anas, Nirwana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2022)
Learning activities in the new normal era in schools are starting to re-run a different learning process from before which must create creative learning so that it can produce outstanding students. Discovery learning-based worksheets are intended to provide direct learning knowledge and meaningful learning process processes so that they are able to direct students to find learning concepts. The purpose of this research is to produce LKPD-oriented learning material discovery in the plant world which is declared feasible, practical, and effective in its use in the process of learning activities. The development model in this study is 4D which consists of 4 stages, namely define, design, development, and disseminate, research subjects for students of 1st class (X IPA 1) of Senior High School of SMA Negeri 2 Rantau Selatan. The research instruments are expert & media expert validation sheets on feasibility testing, practitioner validation sheets to determine practicality, as well as pretest and post-test sheets and student response sheets for effectiveness testing. The results of the study prove that the discovery learning-oriented worksheets developed are declared very feasible with a percentage of 85.5%, very practical with a percentage of 93.5%, and very effective with an increase in learning in the medium category which has been tested with n-gain with a score of 0, 5 and the student's response was very good with a percentage of 82.4%. The results of the study concluded that the discovery of learning-oriented student worksheets that were developed was very feasible, very practical, and very effective in their use in the learning process